Antioxidant Potential of Some Asteraceae Bercht. & J. Presl. Representatives - Shymanska, Oksana; Vergun, Olena; Fishchenko, Valentyna; Rakhmetov, Dzhamal (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Asteraceae Bercht. & J. Presl. is a large family of plants with a different direction of use, among which are medicine, decorative, dietary crops that widely have used in human life. Plant raw material of these plants is a source of biologically active compounds with numerous biological activities such as antioxidant, antimicrobial, anti-inflammatory, etc. This study was aimed to evaluate the antioxidant potential of selected plants from Asteraceae: Bidens ferulifolia (Jacq.) Sweet, Echinacea purpurea (L.) Moench, Rhaponticum carthamoides (Willd.) Iljin, Silphium asteriscus L., S. lacinatum L., S. perfoliatum L., S. trifoliatum L. Raw collected from the collection of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (NBG) in the stage of budding and flowering. Determination of the antioxidant activity of investigated plants conducted by DPPH free radical scavenging activity. In this case, 1 g of dried and milled plant raw extracted in methanol and water in volume 25 ml and 100 µl of filtrate mixed with 3.9 ml of a radical solution. The optical density of the plant extracts measured using the spectrophotometer Unico 2800 (Russia) at the wavelength of 515 nm. Results expressed in % of inhibition. The DPPH free radical scavenging activity of methanol extracts of Bidens ferulifolia was 72.27–86.69 %, E. purpurea of 31.19–75.92 %, Rh. carthamoides of 56.31–73.14 % and Silphium spp. from 34.86 to 92.51 %. This parameter in water extracts was for Bidens ferulifolia 14.68–62.07 %, E. purpurea of 45.47–68.90 %, Rh. carthamoides of 52.61–79.05 %, Silphium spp. from 14.88 to 93.47 %. Thus, a study of the inhibition ability of different extracts of selected Asteraceae plants from NBG demonstrated the antioxidant potential of investigated plants than can be used for further study. Also, raw of these plants can be recommended for farther pharmacological investigations and as useful forage plants.